Polska bibliografia antyku chrześcijańskiego 2022. Z uzupełnieniami za rok 2021 - Pawlak, Adam (Vox Patrum, 2023)
Every year Vox Patrum publishes a bibliography of Christian antiquity, presenting the publications of Polish authors from the previous year. The bibliography is divided into 13 thematic categories and the names of the ancient authors to whom the publications refer.